2001
DOI: 10.1063/1.1391399
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of space charge in conjugated polymers

Abstract: We demonstrate the pyroelectric effect in a conjugated polymer, poly(2,5-pyridinediyl) (PPY), and we use the laser intensity modulation method (LIMM) to resolve the spatial distribution of electric field and space charges inside a 5 μm Au/PPY/Au sandwich device. The pyroelectric signal shows hysteresis behavior with respect to the applied bias indicating permanent storage of injected charges. From the analysis of the LIMM spectra we conclude that application of a bias leads to the accumulation of space charges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…18 In Fig. 5, we show that the charges stored in the polymer layer can make the device work as a data storage device.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…18 In Fig. 5, we show that the charges stored in the polymer layer can make the device work as a data storage device.…”
Section: Resultsmentioning
confidence: 97%
“…17 Such a phenomenon in polymers has been explained in terms of expansion/reduction of the depletion layer at the metal/polymer interface that thereby induces a low/high conducting state in the layer. In other recent work, in demonstrating the pyroelectric effect in conjugated polymers, 18 it has been shown that a spatial distribution of accumulated space charges can be retained in a polymer layer by applying voltage. In this article, we present the results in which poly ͓3-͑6-methoxyhexyl͒ thiophene͔ ͑P6OMe͒ has been used in a nonvolatile data storage device.…”
Section: Introductionmentioning
confidence: 98%
“…2) seems to be due to the quenching of triplet population by charge carriers. It is well known that under the application of a bias voltage a fraction of the injected charge carriers is trapped near the interface regions of the polymer layer and the electrodes leading to accumulation of space charge and thus to local changes of the internal electric field [8][9][10][21][22][23]. Pinner et al [8] reported that the trapped charge carriers give rise to a sharp discharging current spike (of the order of s) after the device is turned off.…”
Section: P H Y S I C a L R E V I E W L E T T E R S Week Ending 28 Marmentioning
confidence: 99%
“…On the one hand, there is a large body of work on bulk devices, in the simplest case consisting of an organic layer, with a typical thickness d of 100 nm, sandwiched between two metallic electrodes [1,2]. Obviously, the spatial resolution is extremely limited in such experiments [3,4]. On the other hand, highly local techniques like scanning-tunneling microscopy (STM) are often used for the investigation of the electronic structure of individual molecules [5].…”
mentioning
confidence: 99%